A systemic overreaction to years versus decades of warming in a subarctic grassland ecosystem - Walker, Tom W.N.; Janssens, Ivan; Weedon, James T.; Sigurdsson, Bjarni D.; Richter, Andreas; Peñuelas, Josep; Leblans, Niki; Bahn, Michael; Bartrons, Mireia; De Jonge, Cindy; Fuchslueger, Lucia; Gargallo-Garriga, Albert; et al. (Nature Ecology & Evolution, 2020)
Abstract: Temperature governs most biotic processes, yet we know little about how warming affects whole ecosystems. Here we examined the responses of 128 components of a subarctic grassland to either 5-8 or >50 years of soil warming. Warming of >50 years drove the ecosystem to a new steady state possessing a distinct biotic composition and reduced species richness, biomass and soil organic matter. However, the warmed state was preceded by an overreaction to warming, which was related to organism physiology and was evident after 5-8 years. Ignoring this overreaction yielded errors of >100% for 83 variables when predicting their responses to a realistic warming scenario of 1 degrees C over 50 years, although some, including soil carbon content, remained stable after 5-8 years. This study challenges long-term ecosystem predictions made from short-term observations, and provides a framework for characterization of ecosystem responses to sustained climate change. Comparing grassland ecosystem responses of 128 biotic and abiotic variables to geothermal warming, the authors find that short-term (5-8 years) responses are poor predictors of change over the long term (>50 years).